Preliminary characterisation of LiAsF6 hybrid polymer electrolytes for electrochromic devices - Rodrigues, L. C. (2011)
In this exploratory study the results of characterisation of a poly(oxyethylene) (PEO)/siloxane hybrid network electrolyte doped with lithium hexafluoroarsenate (LiAsF6) are described. In accordance with convention, the lithium salt concentration is expressed in terms of the number of oxyethylene units in the organic component of the host network per Li+ ion guest species. Samples of solvent-free electrolytes were prepared with a range of guest salt concentration using the sol-gel process. Hybrid materials based on LiAsF6, were obtained as mechanically robust, flexible, transparent and completely amorphous films and characterized by conductivity measurements, thermal analysis and electrochemical stability. Preliminary characterisation of electrochromic devices (ECDs) incorporating optimised LiAsF6-doped di-ureasil compositions have confirmed that these electrolytes perform satisfactorily as multifunctional component layers in this application.